Computerized accounting : - Hearing, Sylvia (Prentice-Hall, 1996)
This book is a comprehensive instructional and learning resource that has been designed to respond to the growing business trend toward the adoption of Windows applications. It is designed to provide readers with a basic knowledge of how computerized accounting systems function and to prepare them to work with any accounting software package. Provides extensive assignment material — tutorials, questions, exercises, and three comprehensive practice sets; introduces chapter material in an extensively illustrated, step–by–step, tutorial format. Readers can then apply the information to more challenging in-text exercises and comprehensive practice sets. Realistic Source Documents, designed like real business documents, illustrate transactions throughout the text. Readers see source information like they would in a real business environment.